Benzoquinone-bridged Co2 complexes with different magnetic anisotropy induced by solvent molecules. Issue 11 (16th February 2017) - Cao, Wenhai; Zhu, Xiaoquan; Liu, Pengfei; Su, Shaodong; Hu, Shengmin; Wen, Yuehong; Wu, Xintao; Sheng, Tianlu
Abstract : The new benzoquinone-bridged Co2 complexes with different magnetic anisotropy induced by acetonitrile and water molecules are reported. Abstract : The first example of discrete small molecular compounds with different magnetic anisotropy induced by solvent molecules, benzoquinone-bridged Co2 complexes, [(TPyA)2 Co2 (L)]·solvent (L = 2, 5-dibromo-3, 6-dihydroxy-1, 4-benzoquinone, solvent = CH3 CN and H2 O), has been prepared and fully characterized.